Climate change and vulnerability of agribusiness: Assessment of climate change impact on agricultural productivity - Mohapatra, Shruti; Mohapatra, Swati; Han, Heesup; Ariza-Montes, Antonio; López-Martín, Maria del Carmen (Frontiers in Psychology, 2022)
The current study has mapped the impact of change in different climatic parameters on the productivity of major crops cultivated in India like cereal, pulses and oilseed crops. The vulnerability of different climatic indicators like exposure, sensitivity and adaptive indicators along with its different components has been studied. The data were collected for the past six decades starting from 1960 to the year 2020. The analytical tools like Tobit regression model and Principal Component Analysis were used for the findings which has portrayed that among the climatic parameters, increase in temperature coupled with huge variations in rainfall and consistent increase in CO2 emission have posed negative impact by reducing the crop productivity particularly in cereals (26 per cent) and oilseed (35 per cent). Among all the factors, the adaptive factors like cropping intensity, agricultural machinery and livestock density coupled with sensitivity factors like average operational land holding size, productivity of cereals and the exposure indicators like Kharif (June-September) temperature, heavy rainfall and rate of change in maximum and minimum Rabi (October-February) temperature have contributed maximum towards the vulnerability. The agribusiness model for being more inclusive should pay attention to small and remote farmers coupled with provision of inclusive finance which could be possible by adoption of climate smart financial innovations that can serve the underserved segments and help reaching the target of sustainable and inclusive agribusiness model. Though the political, social and economic components could empower the adaptive capacity of farmers but the political measure still has a major role in providing a healthy status to agriculture in India through tailored adaptive approaches like adoption of craft climate adaptation program, dilating the irrigation coverage and location centric management options. Hence the multidisciplinary and holistic approaches are worth emphasized for evaluating the future impacts of change in climate upon Indian Agriculture.